DESIGNING FRAMEWORK FOR IT START-UP SUSTAINABLE BUSINESS: INTERNAL AND EXTERNAL ENVIRONMENT APPROACH - Anastasia (CV. Radja Publika, 2026)
Business today operates in high digitalized and dynamic condition that creates challenge for start-up business with low competitiveness and resources. This study looks at internal and external environment factors to understand how business can sustain in challenging environment. This study uses a mix method research design combining qualitative and quantitative approaches. Data were collected through in-depth interviews with several stakeholders to understand their preferences and expectations. The collected data was analyzed to identify key driver factors. The qualitative output was further analyzed using strategic management approach including resource-based theory and porter’s five force analysis. These approaches were used to robust the output. This study found six key driver of IT start-up sustainable business. These key drivers are commercial value, trust and risk assurance, governance and communication clarity, incident resolution and SLA reliability, proactive service improvement, service responsiveness, and technical capability. Moreover, PT Cariva Mitra Inovasi as case study object is perceived positively in communication, collaboration, reporting, incident handling, SLA reliability, proactive monitoring, responsiveness and technical support. This study contributes to strategic marketing literature and stakeholders on improving their sustainable business framework.